2023
DOI: 10.3390/s23156808
|View full text |Cite
|
Sign up to set email alerts
|

Application of Silicon Nanowire Field Effect Transistor (SiNW-FET) Biosensor with High Sensitivity

Huiping Li,
Dujuan Li,
Huiyi Chen
et al.

Abstract: As a new type of one-dimensional semiconductor nanometer material, silicon nanowires (SiNWs) possess good application prospects in the field of biomedical sensing. SiNWs have excellent electronic properties for improving the detection sensitivity of biosensors. The combination of SiNWs and field effect transistors (FETs) formed one special biosensor with high sensitivity and target selectivity in real-time and label-free. Recently, SiNW-FETs have received more attention in fields of biomedical detection. Here,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 118 publications
0
4
0
Order By: Relevance
“…The bonding is verified by measuring the resistance change in the SiNWs before and after the bonding process. It was confirmed that the SiNW-based biosensor could detect amplicons at concentrations below 10 fM within 30 min [21].…”
Section: Current Application Of Epitaxial Semiconducting Nanostructuresmentioning
confidence: 67%
“…The bonding is verified by measuring the resistance change in the SiNWs before and after the bonding process. It was confirmed that the SiNW-based biosensor could detect amplicons at concentrations below 10 fM within 30 min [21].…”
Section: Current Application Of Epitaxial Semiconducting Nanostructuresmentioning
confidence: 67%
“…Although CNT FET possesses numerous advantages over traditional silicon and other semiconductor materials, their widespread adoption has been hindered by the technology's high production cost [18]. Nanowire Field Effect Transistor (NW FET) has the potential to replace the conventional MOSFET where the channel is made of nanowire [19] [20].The dimension of this nanowire is considered to be 0.5nm. Various materials such as silicon, germanium, composed III-V materials, and II-IV materials are used for the channel.…”
Section: Emergence Of Various Semiconductor Devices Over Mosfetmentioning
confidence: 99%
“…Highly selective detection and quantitative analysis of biomolecules can be achieved by designing and constructing nanomaterials on the nanoscale, improving the synthesis methods of nanomaterials, 19 and constructing biosensors with multifunctionality and high sensitivity from nanomaterials. 20 Because of these advantages, nanomaterials have been increasingly used in the field of biosensing. 21,22 The combination of nanotechnology and biosensors shows broad application prospects in the current medical diagnostic field.…”
Section: Introductionmentioning
confidence: 99%